Efficacy and safety of vonoprazan versus proton pump inhibitors in the treatment of peptic ulcer disease: a systematic review and network meta-analysis for randomized controlled trails - Tian, Lidi; Xiang, Dan; Yue, Feili; Li, Runjie; Zhou, Youping (Frontiers in Nutrition, 2024)
Background and Aims Vonoprazan, a novel acid suppressant, has been employed in the treatment of peptic ulcer disease in recent years. However, the efficacy and safety of vonoprazan versus proton-pump inhibitors remains controversial. To address this gap, a systematic review and network meta-analysis were conducted to evaluate the efficacy and safety of vonoprazan in comparison with various proton-pump inhibitors.Methods Randomized controlled trials that met selection criteria in PubMed (Medline), EMBASE and the Cochrane Library were searched up to July 15, 2024. The primary outcome was ulcer healing rate.Secondary outcomes were treatment-emergent adverse events and drug-related adverse events. Effect size on outcomes is presented as odds ratios with 95% confidence intervals.Results Thirty-five randomized controlled trials containing 9,544 participants were included. In terms of the healing rate at 2 weeks, lansoprazole 30 mg ranked first, followed by vonoprazan 20 mg and ilaprazole 10 mg. In terms of the healing rate at 4 weeks, pantoprazole 40 mg ranked first, with rabeprazole 10 mg and lansoprazole 30 mg ranking second and third, respectively. Regarding the healing rate at 8 weeks, lansoprazole 30 mg is demonstrated to be the most efficacious regimen. Moreover, subgroup analysis indicated that lansoprazole 30 mg is the optimal regimen in the treatment of artificial gastric ulcer at 4 and 8 weeks. Importantly, lansoprazole 30mg has fewer adverse reactions and higher safety.The optimal regimen for the treatment of peptic ulcer disease may be lansoprazole 30 mg at 2 and 8 weeks, while pantoprazole 40 mg has demonstrated superior performance at the 4-week when compared to vonoprazan 20 mg. Furthermore, lansoprazole 30 mg has shown to be superior in terms of safety outcomes. These findings, derived from a network meta-analysis, necessitate further research for validation.